Pyoderma Gangrenosum in an Elderly Woman: Case Report - Rina Gustia; Hersa Firda Kartika; Mutia Sari (International Journal of Health and Pharmaceutical (IJHP), 2026)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis that presents with rapidly progressive, painful ulcers and may be diagnostically challenging because it mimics infection, vasculitis, and other ulcerative dermatoses. This report describes an 88-year-old Minang woman who presented with multiple enlarging, painful ulcers on both lower legs and thighs over six months, with significant functional limitation requiring wheelchair use. Dermatological examination showed multiple ulcers with granulation to necrotic bases, irregular margins, and undermined edges, with surrounding erythema and hyperpigmentation. Laboratory evaluation demonstrated mild anaemia with otherwise unremarkable results, while Gram staining showed no bacteria. Dermoscopy revealed irregular ulcer borders with yellow-brown crusting on an erythematous background. Histopathology supported ulcerative PG by demonstrating epidermal hyperplasia with acantholysis, inflammatory cell infiltration including polymorphonuclear leukocytes and lymphocytes, mixed dermal infiltrate, and evidence of vascular destruction. The patient was treated with systemic methylprednisolone alongside topical wound care (saline compresses, topical antibiotics, and topical corticosteroids), resulting in reduced pain and lesion improvement at two-week follow-up with no new ulcers. This case highlights the importance of recognising characteristic clinical features, excluding infection, and using histopathology to support diagnosis, particularly in elderly patients where disease burden and complications may be greater and management must prioritise gentle wound care and avoidance of trauma.